Perspectives of frontline health workers on transition from development assistance for health in Ghana: A qualitative study. - Sandra Appiah-Kubi; Wenhui Mao; Augustina Koduah; Genevieve Cecilia Aryeetey; Osondu Ogbuoji; Justice Nonvignon (Public Library of Science (PLoS), 2022)
Many Low-income countries depend on development assistance for health (DAH) to finance the health sector. The transition of these countries to middle-income status has led to reduction in effective aid from development partners while these countries are expected to graduate from global funding agencies such as Gavi the vaccine alliance, with implications for service delivery. The aim of this study was to explore the perspectives of frontline health workers regarding the implications of Ghana's transition to middle-income status on service delivery, the likely impact and opportunities it presents to the country. This exploratory qualitative study employed in-depth interviews to collect data from 16 health workers at three hospitals in the Greater Accra Region; one at the regional level and two at the district level. The study was conducted from December 2019 to July 2020. Data from interviews were transcribed, coded and analysed using thematic analysis in NVivo Qualitative Analysis Software version 12. The level of awareness among frontline workers about the transition and decline in DAH was generally low. Nonetheless, frontline health workers perceived that the country seems inadequately prepared for transition as donors continue to be major financiers for the sector and even for emergencies such as the current COVID-19 global pandemic. Potential challenges facilities would face due to transition may include difficulty in funding health programs, human resource challenges and delays in logistics and medicines. The implications for these will be poor health outcomes, defective monitoring and evaluation, and lapses in training programs. In addition, the perceived barriers to transition identified were poor management of resources, political interference and lack of technical expertise. While opportunities such as improvement of the health sector prioritization and efficiency, private sector involvement and autonomy could be gained. Gaps in the health intervention monitoring resulting from DAH transition could pose affect health outcomes, particularly in respect of HIV, tuberculosis and malaria. The country's preparedness to transition from DAH could be better improved with development of a clear transition plan agreed by stakeholders, including government and in-country development partners. For the health sector, the eligibility for DAH transition should not simply be based on economic growth, but importantly on a country's ability to sustain ongoing and upcoming health programs.